Evaluation of the overstrength factor for nonstructural component anchorage into concrete via dynamic shaking table tests. (May 2017) - Johnson, Timothy P.; Dowell, Robert K.
Abstract: In ACI 318-11 and ASCE/SEI 7-10 an overstrength factor, Ω0, was introduced for the seismic design of nonstructural building component anchorage into concrete. Though implemented into these codes with the same mechanisms as the overstrength factor for building structures, the rationale behind its inclusion for anchorage was fundamentally different. The primary intent of this factor is twofold: to encourage the use of "ductile" anchorage systems – defined in ACI 318 provisions – by applying a penalty factor to "non-ductile" anchors, and to increase design forces on "non-ductile" anchors to more representative of design-level loading. For ductile systems, a value of Ω0 =1 is permitted, though for non-ductile systems values of Ω0 =2.5 and Ω0 =1.5 are assigned based on component Rp values greater than or less than 2, respectively. These values, however, along with the suggested relationship to component Rp values, were not experimentally established. Work has been ongoing at SDSU since 2011 to characterize this overstrength factor, including two years of full-scale dynamic structural testing using an idealized nonstructural component and several different anchor types on a shaking table. This paper presents a summary of the structural testing performed targeting appropriate Ω0 values, as well as discussion on ductility as it applies to overstrength in anchorage systems. Highlights: Overstrength factor for anchorage into concrete of nonstructural components. Shaking table testing of nonstructural component anchorage. Ductile and non-ductile anchors in concrete. Evaluation of code seismic demands for nonstructural component anchorage into concrete.